Contribution of Tamil literature to moral education - Vellachami, P. (2014)
The purpose of this article is to show the importance of Indian Literature in Moral Education. It plays an important role in building and instilling positive values among secondary students. Moral education is a combination of literacy and moral values. Students need to have the mental, physical, moral and emotional capacity for the betterment of the society at large. It will be a great achievement if every individual is a worthy person. Story and novels are modes to communicate character and background events, which is an effective way to nurture students and instill moral values among readers. Readers will be able to appreciate the values, and it will be forever in their minds. It should be noted, educated or not a reader should be able to appreciate moral values that he or she has read, and the end effect is that it should revitalize their souls. As humans we naturally use values to guide us in our daily actions